Comparison of MARC Serials, NSDP, and ISBD-S - Pulsifer, Josephine S. (Information Technology and Libraries, 1973)
Briefly characterizes and compares the specifications for serial records of the MARC Serials Distribution Service, the National Serials Data Program, and the International Standard Bibliographic Description for Serials. Both data content and, where applicable, machine format are analyzed.